Strategi Pengelolaan Ekowisata Hutan Mangrove Desa Segarajaya Kecamatan Tarumajaya Kabupaten Bekasi - Ramadhanti, Iqraini Azzahra; Syaban, Moh. Balya Ali (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims is to dertermine the right management strategy for ecotourism mangrove forests in Desa Segarajaya. the research method used are quantitative descriptive reseach method. Population in this study are local communities, visitors, and managers who carrries out tourism activities. Management of mangrove forest ecotourism in Desa Segarajaya has decreased after Covid-19. Based on this, the aim of this research was seeking the right strategy for managing mangrove forest ecotourism in Desa Segarajaya , Kecamatan Tarumajaya , Kota Bekasi. Information were collected by carried out on the aspirations of visitors, communities, and ecotourism managers. The questions are about tourist attractions, community participation, and perception in the management of mangrove forest ecotourism in Segarajaya Village. Subsequent, the data is analyzed using SWOT.